PERENCANAAN STRATEGIS DALAM MENJALANKAN BISNIS - Anna Probowati (SEGMEN Jurnal Manajemen dan Bisnis, 2006)
There are some reasons which base the importance of strategic planning in performing bussiness. In unsure condition, the existance of tight competition growth, and the changing of environment this recent year, requires every organization to perform their bussiness should be arranging their strategic plans. An organization must be continously to do the changes toward the reconstruction by giving attention in strategic planning dimension which has orientation for getting the goal. By understanding the determined goal, a company must be understanding many kinds of strategic planning.   Keywords: Strategic planning, dimension, goal, many kinds of strategic planning